Odonata Diversity Around the Arfak Mountains, West Papua - Keliopas Krey; Ade Rahayu Pattiran; Agustinus Kilmaskossu; Yance de Fretes (Badan Penelitian dan Pengembangan Provinsi Papua Barat, 2020)
West Papua is known to harbor high biodiversity and endemicity. Odonata is one taxon that has a high diversity and endemism and plays an important role as an environmental bioindicator. As with many other taxa, field research on the diversity, distribution, and habitat of dragonflies is still very limited in West Papua. Yet, its habitats are under threat due to forest and land conversion for infrastructure developments. This study was designed to document the diversity of Odonata around the Arfak Mountains; especially in Uyehegbrik Village (Prafi District), Hijou Village (Neney District) and Anggra Village (Minyambou District). Data was collected using the purposive sampling technique. The Shannon Diversity Index and t-test were used to calculate and compare species diversity at each research location; and Sorensen Index was used to analyze the similarity of species in each location. About 21 species from 7 families were recorded during this study, 10 of which species are likely new. Our main conclusions include: the Shannon Weaner Index (H’) at the study sites 1.43-1.89 indicates moderate diversity; standing water is the main habitat of dragonflies; the temperature has positive, but weak correlation with species diversity and species abundance. Discovery of new species indicates that this area remains understudied.